A Study on the Collaboration Opportunities between Universities and Insurance Industry in Turkey - Yıldırım, İsmail; Çakar, Recep (Advances in Social Sciences Research Journal, 2015)
The collaboration between universities and industry is of utmost importance for both university education and qualified workforce the industry seeks. This study aims to explore the collaboration opportunities between university and insurance industry. Data was collected from 48 insurance agencies operating in the city of Çorum, Turkey. Insurance agencies advice on the collaboration between universities and insurance industry and they want to take part in the curriculum development.